High Charge Mobility in a Tetrathiafulvalene-Based Microporous Metal–Organic Framework - Narayan, Tarun C; Miyakai, Tomoyo; Seki, Shu; Dincă, Mircea (Journal of the American Chemical Society, 2012)
The tetratopic ligand tetrathiafulvalene-tetrabenzoate (H4TTFTB) is used to synthesize Zn2(TTFTB), a new metal–organic framework that contains columnar stacks of tetrathiafulvalene and benzoate-lined infinite one-dimensional channels. The new MOF remains porous upon desolvation and exhibits charge mobility commensurate with some of the best organic semiconductors, confirmed by flash-photolysis-time-resolved microwave conductivity measurements. Zn2(TTFTB) represents the first example of a permanently porous MOF with high charge mobility and may inspire further exploration of the electronic properties of these materials.